Anti-Staphylococci activity of yeast isolates affected by pH of experimental medium - Dabrowska, I.V.; Tkachenko, K.S.; Podgorsky, V.S.; Fomina, M.O. (Фактори експериментальної еволюції організмів, 2015)
The aim of this work was to study the antagonistic activity of yeasts isolates towards various strains of potentially pathogenic bacteria Staphylococcus aureus. Methods. Over 50 yeasts isolates from authentic dairy products and gastrointestinal tract (GIT) of Hucul long-livers from Ukrainian Carpathians were tested for antagonistic activity towards S. aureus strains by using a conventional agar plug method at pH values of wort agar ranging from 5.0 to 7.0. Results. The anti-Staphylococci activity was found in 15.4 % of tested yeast isolates. In general, the best antagonistic activity towards S. aureus was observed for Saccharomyces pastorianus isolated from dairy products followed by GIT isolates Rhodotorula spp. S1 > Debaryomyces hansenii isolates > Candida spp. S11 > Candida magnoliae S13. The majority of yeasts isolates inhibited tested S. aureus strains at pH 6.0–7.0. Conlusions. Anti-Staphylococci performance of yeast isolates was affected by pH values of experimental medium and depended on yeast species and strains. Keywords: yeasts, Staphylococcus aureus, antagonism, pH.